ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI KASUS: PAMELLA EMPAT SUPERMARKET) - Riska Maulani; Yunita Fitri W (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
The purpose of this study to determine the effect of service quality on customer satisfaction simultaneously. The type of research used in this study is quantitative research. This research uses primary data and secondary data. While the sample technique used is a non-probability sample that uses a total sample of 100 respondents. Based on the results of this study, the quality of service consisting of reliability (reliability) X1, tangible X2, X3 responses, assurance and certainty (assurance) X4, and empathy (empathy) X5 affect customer satisfaction (Y) simultaneously or simultaneously.